2005
DOI: 10.1093/hmg/ddi227
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Krebs cycle intermediates and over-expression of HIF1α in tumours which result from germline FH and SDH mutations

Abstract: The nuclear-encoded Krebs cycle enzymes, fumarate hydratase (FH) and succinate dehydrogenase (SDHB, -C and -D), act as tumour suppressors. Germline mutations in FH predispose individuals to leiomyomas and renal cell cancer (HLRCC), whereas mutations in SDH cause paragangliomas and phaeochromocytomas (HPGL). In this study, we have shown that FH-deficient cells and tumours accumulate fumarate and, to a lesser extent, succinate. SDH-deficient tumours principally accumulate succinate. In situ analyses showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
670
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 775 publications
(700 citation statements)
references
References 34 publications
25
670
1
4
Order By: Relevance
“…Subsequent support for the biochemical role of succinate and fumarate in SDH-and FH-deficient tumours came from metabolomic studies of these tumours (Pollard et al, 2005b). It was clearly demonstrated that succinate levels are high in SDH-deficient HPGL tumours and that both succinate and fumarate levels are high in HLRCC tumours.…”
Section: Mechanisms Linking Loss Of Mitochondrial Tumour Suppressors mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent support for the biochemical role of succinate and fumarate in SDH-and FH-deficient tumours came from metabolomic studies of these tumours (Pollard et al, 2005b). It was clearly demonstrated that succinate levels are high in SDH-deficient HPGL tumours and that both succinate and fumarate levels are high in HLRCC tumours.…”
Section: Mechanisms Linking Loss Of Mitochondrial Tumour Suppressors mentioning
confidence: 99%
“…More recently, an extensive gene expression analysis of 76 phaeochromocytomas with different genetic lesions revealed a 'HIF signature' pattern of gene expression in a cluster of phaeochromocytomas with SDHB, SDHD or VHL mutations (Dahia et al, 2005). Interestingly, in the past year, it was shown that FH-deficient tumours also display high vascularity (Pollard et al, 2005a), increased HIFa levels and activity (Pollard et al, 2005b) and increased expression of glycolytic genes (measured by gene profiling) (Vanharanta et al, 2006). These independent studies collectively suggested that pseudo-hypoxia, manifested by high HIF activity under normoxic conditions, is an important factor that links mitochondrial tumour suppressors and cancer.…”
Section: Mechanisms Linking Loss Of Mitochondrial Tumour Suppressors mentioning
confidence: 99%
“…Germline mutations in FH lead to hereditary leiomyomatosis and renal cell cancer and cause loss of function of FH and an accumulation of fumarate within cells. 24 IDH enzymes normally convert isocitrate to a-ketoglutarate. In contrast, tumor-associated IDH1/2 mutants lose the ability to produce a-ketoglutarate from isocitrate and also gain the neomorphic function of converting a-ketoglutarate to 2-hydroxyglutarate, which accumulates to high levels within IDH1/2 mutant cells.…”
Section: -Hydroxymethylcytosine In Sdh-deficient Gistmentioning
confidence: 99%
“…Loss of SDH activity leads to the accumulation of succinate within cells. 24,25 Because of structural similarities between succinate and a-ketoglutarate, succinate is thought to inhibit the activity of a-ketoglutarate-dependent dioxygenase enzymes. 26 In particular, recent work has demonstrated that the TET family of DNA hydroxylases may be inhibited by elevated levels of succinate.…”
mentioning
confidence: 99%
“…Previous studies have shown that the expression of lactate dehyrogenase (Shim et al, 1997) is directly controlled by the c-myc oncogene, whose expression in turn is regulated by STAT3. In fact, a number of studies have shown an inactivation of enzymes involved in Kreb's cycle and a consequent dysfunction of oxidative phosphorylation in human tumors (Pollard et al, 2003(Pollard et al, , 2005Morris et al, 2004). Fumarate hydratase and succinate dehyrogenase B are few examples for these metabolic tumor suppressors (Pollard et al, 2003).…”
Section: Inactivation Of Grim-19 In Cancer I Alchanati Et Almentioning
confidence: 99%